Adapting educational and psychological tests for cross-cultural assessment - Hambleton, Ronald K.; Merenda, Peter Francis, 1922-; Spielberger, Charles Donald, 1927-2013 (L. Erlbaum Associates, 2005)
Critically examines the dos and don'ts in adapting tests for cross-cultural assessment and research, as well as the major theoretical and methodological issues in the adaptation of educational and psychological tests.